Perkawinan dan Agama-agama (Teropong Ulang terhadap Tujuan, Fungsi dan Aturan Perkawinan) - Affiah, Neng Dara (Musawa Jurnal Studi Gender dan Islam, 2004)
Generally speaking, all religions urge their community to start a family through marriage institution. This institution basically has three main goals: to create peacefulness, to avoid sexual relationship outside marriage, and to have offspring. However, these three goals are often interpreted on the basis of man's superiority. In this article, Neng Dara Afifah tries to underline that marriage is not meant to undermine woman as a human being.